Pengaruh Sudut Terhadap Besar Resultan Gaya Vektor: Kajian Eksperimental Menggunakan Praktikum Cookbook Laboratory - Sipayanti, Sipayanti; Naswa Nurhaliza, Ulfi; Lestari, Wulan; Hidayah, Pikiyatul; Malik, Adam (Prodi Fisika FKIP Unram, 2024)
Vectors are fundamental concepts in mathematics and physics that play a crucial role in various scientific and engineering applications. This study investigates the relationship between the angle and magnitude of the resultant force vector using the Cookbook Laboratory practical approach. The experiment involved combining two forces at different angles and measuring the resultant force. The results indicate a linear relationship between the angle and magnitude of the resultant force, suggesting that as the angle increases, the magnitude of the resultant force also increases. However, this finding contradicts the theoretical prediction of an inverse relationship. This discrepancy is attributed to experimental limitations, particularly parallax error, which may have affected the accuracy of the measurements. Further experiments are recommended to minimize parallax error and obtain more accurate results. A thorough understanding of vector concepts and measurement techniques is essential for comprehending the relationship between angle and resultant force magnitude. Keywords: Angle; Cookbook Laboratory; Resultant Force; Vector.